Analysis Of The Implementation Of Village Financial Accounting In The Government Of Kunduran Village, Seluma Timur District, Seluma Regency - Saputra, Sandi; Fitriano, Yun; Subhi, Ramadan (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the implementation of village financial accounting in the Government of Kunduran Village, Seluma Timur District, Seluma Regency, and to evaluate its compliance with Generally Accepted Accounting Principles (GAAP) and the provisions of Law Number 6 of 2014 concerning Villages. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation related to the processes of recording, managing, and reporting village finances. The analysis was carried out by comparing the accounting practices applied in Kunduran Village with the relevant national accounting standards and regulations. The results of the study show that the Government of Kunduran Village has implemented a cash basis accounting system and utilizes the Village Financial System (SISKEUDES) application in its recording and reporting processes. In general, financial transactions are recorded through the General Cash Book, Village Bank Book, and Activity Subsidiary Cash Book, which are in accordance with generally accepted accounting principles. However, several weaknesses were identified, including the absence of fixed asset depreciation, lack of adjusting journal entries, and incomplete presentation of fixed asset values from previous periods. Overall, the implementation of financial accounting in Kunduran Village has been running quite well, although improvements are still needed in technical aspects and the financial literacy of village officials to achieve more accountable and transparent financial management.